2020
DOI: 10.3389/fpsyg.2019.03026
|View full text |Cite
|
Sign up to set email alerts
|

Pacing Strategy Affects the Sub-Elite Marathoner’s Cardiac Drift and Performance

Abstract: The question of cardiac strain arises when considering the emerging class of recreational runners whose running strategy could be a non-optimal running pace. Heart rate (HR) monitoring, which reflects exercise intensity and environmental factors, is often used for running strategies in marathons. However, it is difficult to obtain appropriate feedback for only the HR value since the cardiovascular drift (CV drift) occurs during prolonged exercise. The cardiac cost (CC: HR divided by running velocity) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…This study demonstrated that females ran at a constant pace considering their Kendall's τ was between −0.05 and 0.05 [6]. It was also highlighted that world records are broken using a running strategy based on running speeds below median speed, unlike popular marathoners who run more distance at speeds above the median [9]. This may be due to the fact that lower level runners (>2 h 20 min) run at too high a target that they cannot maintain beyond the 26th km, where the average speed (i.e., final performance) is reduced and is therefore lower than the median speed.…”
Section: Discussionmentioning
confidence: 80%
“…This study demonstrated that females ran at a constant pace considering their Kendall's τ was between −0.05 and 0.05 [6]. It was also highlighted that world records are broken using a running strategy based on running speeds below median speed, unlike popular marathoners who run more distance at speeds above the median [9]. This may be due to the fact that lower level runners (>2 h 20 min) run at too high a target that they cannot maintain beyond the 26th km, where the average speed (i.e., final performance) is reduced and is therefore lower than the median speed.…”
Section: Discussionmentioning
confidence: 80%
“…Time-domain HRV metrics included beats per minute (BPM), SDNN, and RMSSD. Following this, the cardiac cost (CC) i.e., the ratio between BPM and running speed, was computed (Billat et al, 2020). Frequency domain analysis covered the low (0.04−0.15 Hz-LF) and high (0.04−1.5 Hz-HF) frequency components, as well as the ratio between the two bands (LF/HF ratio).…”
Section: Physiological Parametersmentioning
confidence: 99%
“…This approach has an implicit assumption that different participants develop similar levels of fatigue at similar distances during the run, which may not be true for a heterogeneous participant group employing a variety of pacing strategies. Similarly, existing research on the continuous monitoring of heart rate dynamics and cardiac drift (Billat et al, 2019;Gronwald and Hoos, 2020;Gronwald et al, 2021) has generally considered their evolution over the distance of the run. Combined together, these studies investigate the neuromuscular and cardiovascular response to acute fatigue, but not their concurrent evolution and association.…”
Section: Introductionmentioning
confidence: 99%
“…factors. This "wall" is generally believed in the marathon community to occur around the 30 th km but there are some small differences in the scientific literature; i. e., at km 26 [5], km 30 [6] or with the highest probability at km 32 [7]. Although it seems simplistic to determine a single breakpoint, due to the paucity of the available means for measuring continuously the runner's responses (except for heart rate with heart rate monitors and pacing with Global Navigation Satellite System (GNSS)), the influence of the fatigue-induced biomechanical alterations on the occurrence and magnitude of the "wall" remains unclear.…”
Section: Introductionmentioning
confidence: 99%